2001
DOI: 10.1074/jbc.m005085200
|View full text |Cite
|
Sign up to set email alerts
|

Solution Structure and Dynamics of Myeloid Progenitor Inhibitory Factor-1 (MPIF-1), A Novel Monomeric CC Chemokine

Abstract: The sense of taste, or gustation, is mediated by taste buds, which are housed in specialized taste papillae found in a stereotyped pattern on the surface of the tongue. Each bud, regardless of its location, is a collection of ∼100 cells that belong to at least five different functional classes, which transduce sweet, bitter, salt, sour and umami (the taste of glutamate) signals. Taste receptor cells harbor functional similarities to neurons but, like epithelial cells, are rapidly and continuously renewed throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 64 publications
1
27
0
Order By: Relevance
“…For human CCL15 and CCL23, chemokines that share ϳ64% identity, the extra disulfide seems to have a negligible effect on structure. The extra disulfide in these two chemokines links a 3 10 -helical turn just before the first ␤-strand to the C-terminal ␣-helix and does not disrupt the conserved chemokine fold (17,19). In addition, mutational studies with CCL15 have shown that disruption of the extra disulfide has a minimal effect on protein structure (17).…”
Section: Discussionmentioning
confidence: 99%
“…For human CCL15 and CCL23, chemokines that share ϳ64% identity, the extra disulfide seems to have a negligible effect on structure. The extra disulfide in these two chemokines links a 3 10 -helical turn just before the first ␤-strand to the C-terminal ␣-helix and does not disrupt the conserved chemokine fold (17,19). In addition, mutational studies with CCL15 have shown that disruption of the extra disulfide has a minimal effect on protein structure (17).…”
Section: Discussionmentioning
confidence: 99%
“…Chemokines have also been involved in angiogenesis, Th1/Th2 development, and the release of cytokines (46,47). Two CCR1 ligands, CCL3 and CCL23, have been associated respectively with recruitment of monocytes and T cells (12), specific inhibition of myeloid progenitor cells, and activation of monocytes and eosinophils (48). Interestingly, in a CCR1 Ϫ/Ϫ model of chronic allergic asthma, the features of airway remodeling were greatly reduced in CCR1-deficient animals, suggesting an association between CCR1 and the development of airway remodeling (14).…”
Section: Discussionmentioning
confidence: 99%
“…Many chemokines form homodimers or oligomers at high nanomolar to micromolar concentrations (36-39) whereas others exist strictly as monomers (40)(41)(42)(43)(44). For IL-8, MCP-1, MCP-2, and I-309, the monomeric form predominates in solution at physiological (nM) concentrations (32,44,45).…”
Section: Vv-35kda Protein Monomer Binds Monomeric Mcp-1mentioning
confidence: 99%